Magic Tree House Fact Tracker #23 Snakes and Other Reptiles a Nonfiction Companion to Magic Tree House #45 A Crazy Day with Cobras - Osborne, Mary Pope; Boyce, Natalie Pope Murdocca, Sal (Random House New York, 2011)
An illustrated guide to snakes and other reptiles to accompany "A Crazy Day with Cobras," including facts and photographs that reveal whether snakes can really be "charmed," which reptile has the deadliest venom, how to tell the difference between crocodiles and alligators, and more